Analisis Implementasi Sistem Hybrid Learning terhadap Hasil Belajar Peserta Didik - Nina Yuningsih (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The purpose of this study is to analyze the implementation of the hybrid learning system onthe learning outcomes of elementary school students. The research method uses a qualitativeapproach with the type of case study research. This research was conducted at the UPILaboratory Elementary School, Tasikmalaya City. Retrieval of data and information fromthis study through interviews and observation as the main data and documentation assupporting data. The research subjects were principals and high-class teachers at the UPILaboratory Elementary School, Tasikmalaya City. Data were collected and analyzedqualitatively using the triangulation method. The results of this study are described asfollows: 1) The implementation of hybrid learning has a positive impact on learning activitiesand creativity for both teachers and students which is marked by learning innovations,increasing the participation of parents of students as a solution to the situations andconditions faced at this time. pandemic so that the quality of learning is better; 2) Obstaclesin implementing hybrid learning include: requiring additional time, cost, motivation andcreativity both in planning, implementation and evaluation as feedback to improve theimplementation of further hybrid learning. 3) The learning outcomes of students throughhybrid learning have increased, which is indicated by the results of the PJJ learningevaluation being very significant compared to the results of face-to-face learning evaluations.